SELF REGULATORY-BASED WRITING: AN EFFECTIVE TECHNIQUE TO TEACH ARGUMENTATIVE ESSAY VIEWED FROM STUDENTS’ CREATIVITY - Samsul Arifin (Universitas PGRI Madiun, 2013)
The objectives of the research are to identify the effectiveness of Self-Regulated Strategy Development to teach writing, and whether there is an interaction between the strategy and students’ creativity. This experimental study was conducted at one of the universities in Madiun. The population was the third semester students of this university in the academic year of 2012/2013. Cluster random sampling was used to select 238 students for obtaining two classes of sample, and they are randomly classified into two groups: experimental and control group. The instruments of this research were writing test and creativity test. The data were analyzed using Liliefors and Bartlete tests to investigate the normality and homogeneity of the data, and ANOVA and Tukey to test the hypothesis. The research findings show that self-regulated strategy development is more effective than collaborative writing to teach writing; the students having high creativity have better writing skill than those having low creativity; and there is an interaction between the strategy and students’ creativity in teaching writing. Thus, self-regulated strategy development is an effective strategy to teach writing for students at university level. Therefore, it is better for lecturers to implement the strategy to accomodate students’ creativity.